Cultural Intelligence as a Support for Work Performance in National Company Employees and Multinational Company Employees - Santi Pratiwi; Nandang Budiman; Sardin (al-Afkar, Journal For Islamic Studies, 2025)
Cultural intelligence is an important thing to have in every individual in today's globalization era where intercultural interaction situations cannot be avoided, including in the context of the world of work. This study aims to determine whether the level of cultural intelligence in employees of national companies and employees of multinational companies has differences. The research subjects totaled 115 people with purposive sampling as a research technique. with the criteria of employees who are working in national companies or multinational companies. The results showed that there was no significant difference in the results of cultural intelligence between employees of national companies and employees of multinational companies.